The effectiveness of promotional activities made by Danus (M) Sdn Bhd / Azlina Hamzah - Hamzah, Azlina (Faculty of Business and Management, 2007)
This project paper focuses on the use of promotional structures of marketing tools made by Danus (M) Sdn Bhd. These tools include advertising, public relation and publicity. Danus (M) Sdn Bhd use such promotional activities to provide the information to the clients customers and clients use them to obtain the information about the company. Therefore, the main objective of the study is to identify the effectiveness of promotional activities made by Danus (M) Sdn Bhd to attract business clients to use the products and services. Besides that, this study intends to identify the problems of Danus (M) Sdn Bhd facing and detect what kind of support that they need to become successful in their promotional activities. The objective of this research are to identify the significant relationship between advertising, public relation and sales promotion and promotional effectiveness and to determine the strength of Danus (M) Sdn Bhd regarding its promotional activities.